PENGARUH LEVERAGE, KINERJA KEUANGAN, DAN STRUKTUR MODAL TERHADAP FINANCIAL DISTRESS DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) - Cindy Desita Putri; Hwihanus Hwihanus (Journal of Student Research, 2023)
This study aims to determine the effect of Leverage, Financial Performance, and Capital Structure on Financial Distress with Good Corporate Governance as an Intervening variable in Pharmaceutical sub-sector companies listed on the Indonesian Stock Exchange (IDX). The population in this study are pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The method of analysis in this study is path analysis using Smart PLS 2.0 software. The end result of this research is a picture of causation, so this method uses samples and hypotheses. The test results show that Leverage has a significant effect on Financial Distress, Leverage has a significant effect on Good Corporate Governance, Financial Performance has a significant effect on Financial Distress, Financial Performance has a significant effect on Good Corporate Governance, Capital Structure has a significant effect on Financial Distress, Capital Structure has a significant effect on Good Corporate Governance, Good Corporate Governance has a significant effect on Financial Distress, Leverage has a significant effect on Financial Performance, and Capital Structure has a significant effect on Financial Performance.